Rank Order Centroid as a Method to Weight Dimensional Variables for Developing a Composite Index on Policing Activities in Mining and Quarrying Areas - Bhakti Suhendarwan (Publikasi Indonesia, 2024)
Objective: Dimensional variable weighting is required to calculate the composite index of policing activities in mining and quarrying activities. The purpose of weighting is to determine the Ranking and priority of each indicator and dimension, considering that each indicator does not necessarily have the same value in the actual situation. The weighting method used in this study uses a subjective method using expert opinion. Method: The Ranking carried out by experts is then calculated using rank order centroids. The results of this weighting show that expert opinion can be used to aggregate weights with specific values that can be used as weights for each dimension. Conclusion: The results of this study show that weighting by Ranking by experts through subjective methods can be used to compile rankings or weights of variables for index preparation.